Regioselective Ring Opening of Oxetanes Enabled by Zirconocene and Photoredox Catalysis - Aida, Kazuhiro; Ota, Eisuke; Yamaguchi, Junichiro (Synlett, 2023)
Oxetanes are frequently utilized in organic synthesis, both as target products and as fairly reactive intermediates. Whereas ring cleavage of oxetanes through polar mechanisms has been extensively investigated, their radical-based counterparts remain underexplored. We used zirconocene and photoredox catalysis to open an oxetane ring in a radical manner. In our protocol, the reaction selectively delivers the more-substituted alcohols via putative less-stable radicals. This method not only affords the corresponding hydrogenated products, but also provides unique benzylidene acetal products.
Keywords: zirconocene; photoredox catalysis; oxetanes; reverse regioselectivity; C–O bond homolysis; radicals